Effect of Discordant Hip Bone Density on Incident Fracture Risk: A Registry‐Based Cohort Study. (7th September 2022) - Leslie, William D.; Morin, Suzanne N.; Lix, Lisa M.; McCloskey, Eugene V.; Johansson, Helena; Harvey, Nicholas C.; Kanis, John A.
ABSTRACT: The Fracture Risk Assessment Tool (FRAX®) combines clinical risk factors and optionally femoral neck bone density to estimate major osteoporotic fracture (MOF) and hip fracture probability. Hip dual‐energy X‐ray absorptiometry (DXA) simultaneously measures the trochanter and total hip, but these regions are not considered by FRAX. Our aim was to determine whether discordance in trochanter and total hip bone density (defined as ≥1 T ‐score difference from the femoral neck) affects fracture risk adjusted for fracture probability. Using the Manitoba bone density registry, we identified 84, 773 women and men age 40 years or older undergoing baseline hip DXA. The outcomes were incident MOF and hip fracture. Cox regression hazard ratios (HRs) with 95% confidence intervals (CIs) adjusted for baseline fracture probability were used to test the association between hip T ‐score discordance and incident fractures. Hip T ‐score discordance affected more than one in five subjects (trochanter lower in 3.9%, higher in 14.2%; total hip lower in 0.3%, higher in 14.9%). After mean 8.8 years there were 8444 incident MOF including 2664 hip fractures. Discordantly lower trochanter and lower total hip T ‐score (≥1 below femoral neck) was associated with increased risk for MOF (adjusted HRs 1.47 and 1.60) and hip fracture (HRs 1.85 and 2.12), while discordantly higher trochanter and total hip T ‐score (≥1 above femoral neck) was associated with lower risk for MOF (HRs 0.83 and 0.71) and hip fracture (HRs 0.79 and 0.68). In models that examined the trochanter and total hip simultaneously, discordantly lower trochanter T ‐score was associated with increased incident MOF and hip fracture risk (HRs 1.43 and 1.79) whereas discordantly higher total hip T ‐score was associated with lower risk (HRs 0.73 and 0.75). In conclusion, trochanter and total hip regions frequently show T ‐scores that are discordant with the femoral neck. This information strongly affects incident fracture risk independent of fracture probability scores computed with femoral neck bone density. © 2022 American Society for Bone and Mineral Research (ASBMR).